Sexual Violence among University Medical Students in Sumatera, Indonesia - Windasari, Noverika; Fadila, Zurayya (Majalah Kedokteran Bandung, 2025)
Sexual violence is a pervasive issue affecting both adults and children globally, resulting in severe trauma for victims. Due to the power dynamics, this problem also extends to educational institutions, including universities. Therefore, this study aimed to investigate incidents of sexual violence among medical students at a state university in West Sumatra, Indonesia in 2023. A descriptive cross-sectional survey was conducted using a questionnaire distributed to pre-clinical and clinical medical students. A total of 1,170 students were included as respondents, of which 9.66% of them reported experiencing sexual violence. Specifically, 46.% of respondents had previous experience of sexual violence, and 42.5% of these occurred during their time as university students. The most common forms were non-physical sexual violence, accounting for 35% of reported cases, with 30.3% of the perpetrators being strangers. Over half of the victims experienced sexual violence more than once, and only 46.2% of victims reported their experience. This study showed that sexual violence affected medical students, mainly in non-physical forms, with a low reporting rate. Consequently, collaboration between campus leaders and the academic community is crucial to empower victims in participating and creating an environment that is free from sexual violence. Preventive efforts must also be comprehensive, engaging multiple sectors and community, to effectively combat sexual violence in universities.